Abscopal effect in a patient with malignant pleural mesothelioma treated with palliative radiotherapy and pembrolizumab. (March 2021) - Mampuya, Wambaka Ange; Bouchaab, Hasna; Schaefer, Niklaus; Kinj, Remy; La Rosa, Stefano; Letovanec, Igor; Ozsahin, Mahmut; Bourhis, Jean; Coukos, George; Peters, Solange; Herrera, Fernanda G.
Highlights: Abscopal effect is the ability of local RT to induce systemic antitumor effect. Abscopal effect is increasingly frequent with concomitant immunotherapy and RT. Abscopal effect remains a rare observation. We report an abscopal effect in MPM treated with concomitant anti-PD-L1 and RT. Abstract: The abscopal effect describes the ability of locally administered radiotherapy to induce systemic antitumor effects. Although mentioned for the first time in the 1950s, records of abscopal effects, considered to be immune-mediated, are scarce with radiotherapy alone. However, with the continued development and use of immunotherapy, reports on the abscopal effect have become increasingly frequent during the last decade. Here, we report a patient with advanced malignant pleural mesothelioma who had progressive disease while on the anti-PDL1 inhibitor pembrolizumab and showed an abscopal response after palliative radiotherapy.